The effect of backpack carriage on the biomechanics of walking: A systematic review and preliminary meta-analysis - Liew, B.; Morris, Susan; Netto, Kevin (Human Kinetics, 2016)
The aim of this systematic review was to evaluate the impact of bilaterally symmetrical backpack systems borne on the posterior trunk on walking biomechanics, as backpacks represent the most prevalent method of load carriage in the military and civilian population. A search of electronic databases was performed for studies that only investigated posteriorly-borne backpack carriage during level-grade walking (treadmill and over ground). Methodology of studies was assessed, and both meta-analysis and qualitative synthesis were completed. Fifty-four studies were included in this review. In summary, the available literature showed that backpack carriage in walking was associated with an increased trunk flexion angle, increased hip and ankle range of motion, increased vertical and horizontal ground reaction force, increased cadence, and reduced stride length. Several variations in backpack carriage protocols could explain between-study variations in results, including: walking speed, backpack carriage skill level, the use of a hip belt, and posterior displacement of the load away from the trunk. The findings of this systematic review will inform backpack carriage practices in the area of injury risk assessment and physical performance enhancement.